Pengaruh Jam Kerja dan Lama Usaha Terhadap Pendapatan UMKM Produk Lanting Desa Adiraja Kecamatan Adipala Cilacap - Muzaki, Hasan; Hakim; Vidiani, Aisyah (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research discusses the influence of working hours and length of business on income. The research method uses descriptive quantitative data analysis with the variables working hours (X1) and length of business (X2) and income (Y). The sample from this research consisted of 50 traders. The results of data processing state that: Based on the results of multiple liner regression testing, it is proven that the working hours variable has a negative sign, meaning that working hours have no effect on MSME income from lanting products with a regression coefficient value of -0.164. Based on the results of multiple linear regression testing, it is proven that the value of 0.506 in the Length of Business variable is positive, this means that it shows a unidirectional influence between the independent variable and the dependent variable. Based on the results of tests simultaneously or called simultaneous, it shows that the variables of working hours and length of business have an F table value of 2.80. Based on these results, it can be seen that the calculated f value is 13,277>2.80 and the significance value is 0.001<0.005. Thus, it can be concluded that the variables of working hours and length of business have an effect simultaneously